ANALISIS KEPERCAYAAN KONSUMEN, PERSEPSI KEMUDAHAN PENGGUNAAN, DAN PERSEPSI RISIKO TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN E-COMMERCE (Studi Empiris Pada Konsumen Lazada di Semarang) - Indah Novitasari; Retno Hidayati (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to analyze the effect of consumer trust, perceived ease of use, and perceived risko on Lazada e-commerce purchasing decision making in Semarang, so that they can be a review in making strategies to improve purchasing decision making. The population in this study were Lazada consumers in Semarang. Data obtained through a questionnaire form a sample of 170 people with purposive sampling. Then, the data is processed and analyzed using index numbers and multiple linier regression using the SPSS version 25 program, The results showed that consumer trust, perceived ease of use, and perceived risk had significant positive effect on Lazada ecommerce purchasing decicion making, all of which can be accepted.